Acute febrile cholestatic jaundice in children: keep in mind Kawasaki disease. - Taddio, Andrea; Pellegrin, Maria Chiara; Centenari, Chiara; Filippeschi, Irene Pellegrini; Ventura, Alessandro; Maggiore, Giuseppe (J Pediatr Gastroenterol Nutr, 2012)
Kawasaki disease (KD) is characterized by persistent fever in addition to 4 of 5 signs of mucocutaneous inflammation. Although gastrointestinal involvement does not belong to the classic diagnostic criteria, it has been often associated with KD onset. We reviewed patients who were admitted for febrile cholestatic jaundice between 2003 and 2010 in 2 tertiary pediatric care centers. KD was the second most frequent cause (21%) after viral infections. Considering the relative high frequency of this condition, a high index of suspicion of KD should be maintained in patients presenting with febrile cholestatic jaundice.
Keywords: Child; Child, Preschool; Diagnosis, Differential; Female; Fever; Humans; Infant; Jaundice, Obstructive; Male; Mucocutaneous Lymph Node Syndrome; Virus Diseases